Literacy Intervention Strategies for Increasing Kindergarteners’ Letter Sound Fluency and Word Recognition: A Proposed Intervention - Sapequeńa, Alfredo E. (International Journal For Research In Educational Studies, 2020)
This research sought to determine the effectiveness of the following proposed literacy intervention strategies: perfect match, fluency letter wheel, letter flash, familiar word readings, word relay, and fast match in increasing letter sound fluency and word recognition among kinder pupils enrolled in Manggolod Elementary School of Sta. Catalina District III. Forty-two (42) respondents were equally distributed among three groups based on their level of intelligence per academic grades from first to second quarter. The study utilized the standardized Early Grade Reading Assessment (EGRA) as the tool in determining the pre-test and post-test performance of the kinder pupils. The researcher prepared 3 different intervention strategies for letter sound fluency and 3 different intervention strategies for word recognition and administered them to the pupils. To check on the effectiveness of the strategies, a post-test was conducted using EGRA. Results were statistically treated using percentage, weighted mean, t-test for independent data and t-test for dependent data. It was found out that pre-test and post-test performance of the kinder pupils in letter sound fluency and word recognition was generally within satisfactory level. Post-test performance in letter sound fluency and word recognition was also remarkable. There was a significant difference between their pre-test and post-test performance in letter sound fluency word recognition intervention activities. Hence, it is recommended that other schools would use the strategies proposed in this study so to compare the findings of this study.